KAJIAN TEORITIS TENTANG PERILAKU LESBIAN, GAY, BISEKSUAL, TRANSGENDER (LGBT) DALAM PERSPEKTIF PSIKOLOGIS DAN TEOLOGIS - Abd Mukhid (UIN Mataram, 2018)
There are two problems that want to be answered in this research, namely: (1) how is LGBT behavior in a psychological perspective? And (2) how is LGBT behavior in a theological perspective? This study uses a descriptive qualitative approach. Data collection techniques using interview, observation and documentation techniques. The location of the study was carried out in Lesp Backup, Mojokerto Regency with three informants using a purposive sampling technique. The results of the study show that in a psychological and theological perspective: (1) LGBT behavior is not taken from birth, but this behavior can be formed from childhood, such as since school in elementary or middle school or high school; (2) LGBT behavior is a form of deviant sexual behavior; (3) LGBT behavior becomes a lifestyle for the LGBT community; (4) LGBT actors in the social community are able to adjust well; (5) LGBT behavior deviates from the customs and culture of the community; (6) Factors that cause LGBT behavior can be caused by fostering parents in children from childhood; and (7) LGBT behavior can be cured, provided that there is strong intention